Kritik Khaled Abou El Fadl terhadap Penggunaan Hadis Perempuan Sumber Fitnah di Kalangan Islam Puritan - Ach Baiquni (Program Pascasarjana IIQ Jakarta, 2024)
The discourse on women as a source of slander continues from the classical era to the present, this discourse is still contextual even though many researchers have examined this issue, this discourse is motivated by the hadith which states that women are a source of slander, this hadith is then used as a basis for a fatwa by Puritan Islamic groups so that women do not have a role in the public sphere, this issue has led to criticism from Khaled Abou El Fadl. This paper aims to analyze the criticism conveyed by Khaled Abou El Fadl regarding the use of hadith on women as a source of slander that is often conveyed on television, Youtube, fatwas in Islamic circles labeled as puritanical. In addition, this paper also wants to describe the construction of puritan Islam, their understanding, their use of hadith and the theory used by Abou el Fadl about criticizing the use of hadith related to women. While the research method used is qualitative with an analytical descriptive approach so as to obtain the conclusion that the understanding of Puritan Islam in understanding the hadith that is used as their reference in issuing a fatwa tends to be textual, rigid, unwilling to compromise with the ulama then Khaled Abou El Fadl's criticism of the use of hadith is based on five conditions in using hadith as evidence in religion, namely, honesty, diligence, thoroughness, reasonableness and control.